Perubahan Adat Perkawinan Suku Sakai Di Pemukiman Buluh Kasap Kopelapip Kecamatan Mandau - Nila Novia; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Matrimony at the Sakai community settlement Kasap Reed still thick with certain rituals magical scented some years ago. Marriages that occurred in Sakai tribe society at large is usually only done by a virgin girl and a widower with a widow. Rare marriage between a man married to another woman aka polygamy. The reason is based on practical considerations, namely to avoid costly finance life because life bear more than one wife. Moreover, Bathin as a (Chieftain) used a dog or cat as a tool to legitimize marriage ( Parsudi Suparlan , 1993). The objectives to be achieved in this study are : To find out what the marriage stages procession in the Sakai community Settlements Reed Kasap, Kopelapip, District Mandau. To find out what are the factors that cause changes in the mating stages in the Sakai tribe settlements Reed Kasap, Kopelapip, District Saber, Duri. To find out how the public perception of Sakai in Settlements Reed Kasap, Kopelapip, District Saber, Thorns to a change in the system of their marriage.Subjects in this study is one key informants Bagindo Puyan Rajo, which incidentally is the Head of the Sakai tribe at Reed Residential Kasap, and four informants that researchers choose based on certain criteria (purposive sampling).Changes in mating system occurs because of the Sakai tribe motivating factor, ie internal factors and external factors. The internal factors include the religious mindset that has advanced, heterogeneous population, and the desire of the people themselves to change. While external factors include the influence of outside contact with other societies and cultures mixing caused by marriage and so forth.Keywords : Change, Tradition, Marriage, Sakai tribe